Job Satisfaction and Associated Factors among Health Assistants in Bangladesh (Journal of Preventive and Social Medicine, 2026)
Background: Job satisfaction is the foundation of professional life which determines the purposes, efficacy, and identification with the culture of the organization. To determine the level of job satisfaction and associated factors among Health Assistants in Bangladesh.Materials and methods: The cross-sectional study was conducted from January to May 2025 using proportionate multi-stage sampling across 15 districts in all 8 divisions of Bangladesh. The study was carried out in 47 Upazilas across 15 districts in all 8 divisions of Bangladesh. A total of 1181 health assistants were selected, considering a 10% non-response rate. Data were collected via face-to-face interviews using a modified pre-tested semi-structured questionnaire adapted from the QPS (Nordic), mostly based on a 5-point Likert scale. Data were analyzed in SPSS 25 using descriptive statistics and inferential tests including Pearson Chi-Square and correlation analysis to explore associations between key variables.Results: The majority of respondents were aged 30–49 years, had over 10 years of service, and 70.2% had education above HSC. High intrinsic motivation was evident. About 94.2% found their work meaningful, and 87.6% showed strong organizational commitment. Social support was strong, with high peer and supervisory support and low interpersonal conflict. Systemic challenges were severe - 89% reported high job demands, 82.1% faced managerial unpredictability, and 57.9% received inadequate task support. Though direct bullying and abuse were uncommon (experienced by 3% and 2% respectively), their presence helps to create a stressful environment. Correlation analysis revealed that the most powerful negative influence was perceived inequality (r=0.305; r=0.318) whereas a "positive challenge at work" was the strongest positive predictor of motivation (r=0.379 intrinsic; r=0.444 extrinsic). With statistically lower levels of job control (p=0.007) and predictability (p=0.000) than their male counterparts, significant sex differences also appeared in female HAs.Conclusion: Despite high motivation and support, job satisfaction remains fragile due to systemic issues. Sustainable improvement requires structural reforms in healthcare delivery.JOPSOM 2025; 44(2): 22-30